Development of an ontological model for the domain of it enterprise sustainable development - Popereshnyak, Svitlana; Grinenko, Sergiy (Technology audit and production reserves, 2019)
The object of research is the sustainable development of IT enterprises. One of the most problematic places is the specification of the subject area, taking into account the specific activity of the IT enterprise. Today, there is a certain amount of research in the field of sustainable development, however, given the specific nature of the IT enterprise, namely that its main asset is software development, there are no researches related to the analysis of the sustainable development of IT enterprises. That is why, above all, the question arises in the representation of knowledge about the subject area. As a result, it is important to develop a model that displays the domain objects and the links between them. Such a tool is ontologies, which are a formalized representation of domain knowledge. The paper discusses the problem of building an ontology for a subject area of sustainable development of an IT enterprise, which includes the following steps: – justification of the use of ontologies for domain modelling; – a brief description of the basic steps of building an ontology in accordance with the IDEF5 standard. The collection and source analysis for the formation of verbal subject domain specifications. It should be noted that the developed ontology includes three types of representation: verbal, graphic and analytical. Within this paper, only two representations (graphical and analytical) are given. The IDEF5 Schematic Language (SL) was used to graphically represent the ontology, which includes several types of ontology diagrams. In the framework of our study, we used the Composition Schematics, which is a mechanism for graphically representing the composition of ontology classes. For analytic representation, predicate calculations were used, because with increasing and refining the ontology of the subject area, this mathematical apparatus ensures the reliability of the results. The developed ontology involves refinement and expansion in accordance with the requirements of projects where this ontology will be used, for example, to develop an expert system for solving problems of the subject area.